Design and Synthesis of 2-Methyl and 2-Methyl-4-NitroImidazole Derivatives as Antifungal Agents: Synthesis of new imidazole derivatives - Soghra Khabnadideh,; Zahra Rezaei,; Mohammad Javad Heiran,; Hesamedin Shobeiri,; Ali Khalafi-Nezhad,; Keyvan Pakshir, (Iranian Journal of Pharmaceutical Sciences, 2009)
Two series (aand b) of N-substituted heteroaromatic compounds related to clotrimazole were synthesized. Imidazole ring of the clotrimazole was replaced by 2-methylimidazole in series a, and by 2-methyl-4-nitroimidazole in series b. O-cholortrityl moiety of clotrimazole was also replaced by trityl, mono or dimethoxy trityl. Chemical structures of all the new compounds were confirmed by spec-trophotometric methods. These compounds docked into the active site of MT-CYP51(PDB code, 1E9X) using Autodock tools software which showed good affinity for the enzyme. Antifungal activities of these compounds were evaluated against Trichophyton mentagrophytes, Microsporum gypseumand Candida albicans using SC, SCC and PDAas media, CHCl3and DMSO as solvents and agar dilution assay as method. In this method 1(4-methoxyphenyl-diphenylmethyl)-2-methylimidazole (2), 1[bis-4-methoxyphenyl-phenylmethyl]-2-methyl imidazole (3) and1[4-methoxyphenyl-diphenylmethyl]-2-methyl-4-nitroimidazole (5) showed morethan 75% activity against fungi. In the second step all of the derivatives also were evaluated against Trichophyton rubrum, Microsporum canisand Epidermaphyton floccosum using PDAmedium by agar dilution method. Compound 2showed morethan 75% activity by this method. Then the most active analogue (2) was tested in RPMI 1640 medium which showed desirable biological activity in comparison to clotrimazole.